2009
DOI: 10.1002/humu.21020
|View full text |Cite
|
Sign up to set email alerts
|

Gene conversion causing human inherited disease: Evidence for involvement of non-B-DNA-forming sequences and recombination-promoting motifs in DNA breakage and repair

Abstract: A variety of DNA sequence motifs including inverted repeats, minisatellites, and the χ recombination hotspot, have been reported in association with gene conversion in human genes causing inherited disease. However, no methodical statistically-based analysis has been performed to formalize these observations. We have performed an in silico analysis of the DNA sequence tracts involved in 27 non-overlapping gene conversion events in 19 different genes reported in the context of inherited disease. We found that g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 80 publications
1
82
0
Order By: Relevance
“…To date, a number of such gene conversion events have been reported for genes mapping in paralogous LCRs (Chuzhanova et al 2009), e.g., SMN1 and its very highly similar (99.99%) copy SMN2 (Lefebvre et al 1995), responsible for autosomal recessive spinal muscular atrophy (SMA, MIM# 253300), GYPE and GYPA genes in chromosome 4q31, associated with blood group MN (MIM# 111300) (Huang et al 2000), and NCF1B and NCF1, mutated in patients with chronic granulomatous disease (MIM# 233700) (Vázquez et al 2001). For pachyonychia congenita type 2 (MIM# 167210) (Hashiguchi et al 2002), we found DP-LCRs with fraction matching 94.99% (chr17:28,894,052-28,902,101 and chr17:39,776,063-39784174, separated by 10.874 Mb) and harboring the KRT17P3 and KRT17 genes.…”
Section: Gene Conversionsmentioning
confidence: 99%
“…To date, a number of such gene conversion events have been reported for genes mapping in paralogous LCRs (Chuzhanova et al 2009), e.g., SMN1 and its very highly similar (99.99%) copy SMN2 (Lefebvre et al 1995), responsible for autosomal recessive spinal muscular atrophy (SMA, MIM# 253300), GYPE and GYPA genes in chromosome 4q31, associated with blood group MN (MIM# 111300) (Huang et al 2000), and NCF1B and NCF1, mutated in patients with chronic granulomatous disease (MIM# 233700) (Vázquez et al 2001). For pachyonychia congenita type 2 (MIM# 167210) (Hashiguchi et al 2002), we found DP-LCRs with fraction matching 94.99% (chr17:28,894,052-28,902,101 and chr17:39,776,063-39784174, separated by 10.874 Mb) and harboring the KRT17P3 and KRT17 genes.…”
Section: Gene Conversionsmentioning
confidence: 99%
“…Top1 nicks the DNA, forms a transient covalent bond with the DNA through its tyrosine residue, rotates the DNA around the helix, and then religates the cleaved ends; this set of actions can result in an increase or decrease of the superhelix (16). Notably, the active transcription of repeat sequences is predicted to form non-B DNA structures (17,18). When the DNA has aberrant structures like non-B DNA, rotation around the helix may be inhibited; thus, the cleavage by Top1 may be irreversible and trigger genome instability ( Fig.…”
Section: An Evolutionary View Of the Mechanism For Immune And Genome mentioning
confidence: 99%
“…These triplet repeats are usually located within a transcription unit and are probably prone to form non-B structures similarly to TAM (18). Recently, triplet repeat contraction was shown to be caused by Top1 (3).…”
Section: An Evolutionary View Of the Mechanism For Immune And Genome mentioning
confidence: 99%
“…It has been motivated that the recombination system that carries out rearrangements may be a significant evolutionary force, perhaps not limited to rearrangements only at antigenreceptor loci (Roth 2000) (Chuzhanova et al, 2009). Genomic changes in V-gene structure, created by RAG recombinase acting on germline recombination signal sequences, led variously to the generation of fixed receptor specificities, pseudogene templates for gene conversion, and ultimately to Ig sequences that evolved away from Ig function (Hsu et al, 2006).…”
Section: Cfs Rag Genes and Transposable Elements (Te's)mentioning
confidence: 99%